Metrology Standards for Quantitative Imaging Biomarkers - Sullivan, Daniel C; Obuchowski, Nancy A; Kessler, Larry G; Raunig, David L; Gatsonis, Constantine; Huang, Erich P; Kondratovich, Marina; McShane, Lisa M; Reeves, Anthony P; Barboriak, Daniel P; Guimaraes, Alexander R; Wahl, Richard L (Radiology, 2015)
Although investigators in the imaging community have been active in developing and evaluating quantitative imaging biomarkers (QIBs), the development and implementation of QIBs have been hampered by the inconsistent or incorrect use of terminology or methods for technical performance and statistical concepts. Technical performance is an assessment of how a test performs in reference objects or subjects under controlled conditions. In this article, some of the relevant statistical concepts are reviewed, methods that can be used for evaluating and comparing QIBs are described, and some of the technical performance issues related to imaging biomarkers are discussed. More consistent and correct use of terminology and study design principles will improve clinical research, advance regulatory science, and foster better care for patients who undergo imaging studies.